Straight path and it effect on acts of community members (Journal of Human Sciences, 2021)
Because this era contains massive suspicions and ramifications it is our responsibility to search and find the  satisfation of  our lord the acts that blesses god will make us good model for building a good society surat  la anam provide us with examples of such acts for the researcher chose to study this surah and she aduices  whomever is interested to research widly and to study deeply this surah. these concepts included the path in language and idiomatically and the path effects the behavior of the  individual end society. Then surat AL-Anam and the definition or introducing of surat AL-Anam in language end idiomatically. And the behavior in language end idiomatically and its effects on individual and society and it was motivated to knew the straight path that guidy a Muslim to his lord almighty and directing the right  behavior a summed and correct foundation.